WASIAT WAJIBAH UNTUK ANAK ANGKAT PERSPEKTIF SIYĀSAH AL-SYAR’IYYAH - Munadi Usman (Indonesian Association of Islamic Family Law Lecturers, 2021)
Provisions of the wajibah testament to adopted child contained in the Compilation of Islamic Law Article 209 verse 1 and 2 constitute a renewal of Islamic inheritance law in Indonesia, but many legal experts doubt the validity of this provision and assume it does not have a clear legal basic in the form of naṣ (maṣadir al- ahkām), the method of istinbath (qaidah al-ahkām) and the purpose or legal implications (maqaṣid al-ahkam). This study aims to verify the validity of the wajibah testament to adopted child with the siyāsah al-shar'iyyah approach. The results of the study showed that the wajibah testament to the adopted child are legal rules that run based on government policy to resolve the issue of inheritance between heirs or persons who have a close relationship with the heir but is prevented from inheriting. The government is making the wajibah testament for adopted child in KHI as a solution to resolve this problem.